Respuesta :

gmany

[tex]2\dfrac{5}{8}+1\dfrac{3}{8}=2+\dfrac{5}{8}+1+\dfrac{3}{8}=(2+1)+\left(\dfrac{5}{8}+\dfrac{3}{8}\right)=3+\dfrac{5+3}{8}\\\\=3+\dfrac{8}{8}=3+1=4\\----------------------\\7\dfrac{1}{4}+2\dfrac{3}{4}=7+\dfrac{1}{4}+2+\dfrac{3}{4}=(7+2)+\left(\dfrac{1}{4}+\dfrac{3}{4}\right)=9+\dfrac{1+3}{4}\\\\=9+\dfrac{4}{4}=9+1=10\\----------------------\\2\dfrac{2}{5}+4\dfrac{2}{5}=2+\dfrac{2}{5}+4+\dfrac{2}{5}=(2+4)+\left(\dfrac{2}{5}+\dfrac{2}{5}\right)=6+\dfrac{2+2}{5}\\\\=6+\dfrac{4}{5}=6\dfrac{4}{5}[/tex]